Pengaruh Persepsi, Tingkat Pendidikan, dan Sosialisasi Terhadap Penerapan SAK EMKM Pada UMKM Wilayah Kota Surabaya - Galuh Artika Febriyanti; Agung Sri Wardhani (Jurnal Ilmiah ESAI, 2018)
The perpetrators of MSMEs generally do not use the standards applicable in the preparation of financial statements. MSME financial statements often use cash basis taken from daily cash mutation sources. The Indonesian Institute of Accountants seeks to contribute to overcome the constraints of MSMEs in the preparation of financial statements by issuing the Financial Accounting Standards of Micro Small and Medium Enterprises (SAK EMKM) and effective from 1 January 2018. SAK EMKM is simple to be implemented easily by MSMEs. The Financial Statements according to SAK EMKM are prepared on the accrual basis. The research took 50. MSMEs in Surabaya using convenience sampling method.  The data used are primary data obtained through questionnaires. This study aims to finding out the hypothesis that the perception of MSMEs in Surabaya against the application of EMKM IFRS had an effect on the application of EMKM IFRSs, testing the education level hypothesis of MSMEs in Surabaya had an effect on the application of EMKM IFRSs, and tested the hypothesis of SAK EMKM dissemination in Surabaya. application of SAK EMKM.  The results showed that partially the perception of MSMEs entrepreneurs has a positive effect on implementation SAK EMKM while the level of education and sozialization has a negative effect. Keywords: Accounting, Education Level, financial reports, MSME, Perception,  SAK EMKM, Sozialization